Rezagos de la lengua Muchik en el ámbito del antiguo corregimiento de Trujillo y su posible uso turístico. - Vera Murga, Iris Jaqueline (2018)
The present thesis report called Remains of the Muchik language in the area of the old Trujillo corregimiento and its possible tourist use, had as a general objective to identify the tourist use of the remnants of the Muchik language in the area of the old district of Trujillo. One of the lags presented by the five districts involved in the present study are the linguistic evidences expressed in anthroponymy and toponymy, manifested in surnames typical of the Muchik language; as well as the names of the Mochica occupation sites and their associated natural elements, respectively; which could be used touristically by generating interpretive tourist routes, which include scripts and Muchik representations. The existence of a lexicon Muchik is another lag that remains in force and adapted to the Castilian language of the inhabitants who currently inhabit the five districts that belonged to the old village of Trujillo and is given by the use of words of Mochica origin in the colloquial speech, which could be used to strengthen their identity with their Mochica ancestors. Also the presence of written sources as existing written documents from the seventeenth century to the present, have allowed the development of research, academic work and dissemination actions that safeguards the Muchik language, thus facilitating learning and interpretation. _x000D_ To study each of the remnants of the Muchik language and its possible tourist use, the Ethnographic method was used; the Genetic method to carry out an analysis of the historical development of the Muchik language and its changes up to the present; In addition, the Interview technique was used, which was applied to history teachers and the president of the society of safeguard of the Muchik language; Likewise, surveys were applied to the inhabitants of the five districts involved.